Frequency-specific Alterations of Large-scale Functional Brain Networks in Patients with Alzheimer's Disease - Qin, Yuan-Yuan (Chin Med J (Engl), 2015)
BACKGROUND: Previous studies have indicated that the cognitive deficits in patients with Alzheimer's disease (AD) may be due to topological deteriorations of the brain network. However, whether the selection of a specific frequency band could impact the topological properties is still not clear. Our hypothesis is that the topological properties of AD patients are also frequency-specific. METHODS: Resting state functional magnetic resonance imaging data from 10 right-handed moderate AD patients (mean age: 64.3 years; mean mini mental state examination [MMSE]: 18.0) and 10 age and gender-matched healthy controls (mean age: 63.6 years; mean MMSE: 28.2) were enrolled in this study. The global efficiency, the clustering coefficient (CC), the characteristic path length (CpL), and “small-world” property were calculated in a wide range of thresholds and averaged within each group, at three different frequency bands (0.01–0.06 Hz, 0.06–0.11 Hz, and 0.11–0.25 Hz). RESULTS: At lower-frequency bands (0.01–0.06 Hz, 0.06–0.11 Hz), the global efficiency, the CC and the “small-world” properties of AD patients decreased compared to controls. While at higher-frequency bands (0.11–0.25 Hz), the CpL was much longer, and the “small-world” property was disrupted in AD, particularly at a higher threshold. The topological properties changed with different frequency bands, suggesting the existence of disrupted global and local functional organization associated with AD. CONCLUSIONS: This study demonstrates that the topological alterations of large-scale functional brain networks in AD patients are frequency dependent, thus providing fundamental support for optimal frequency selection in future related research.